Analysis Of The Influence Of Product Quality, Lifestyle And Promotional Strategy On The Decision To Purchase Samsung Smartphone Products - Khoirul Anwar; Bord Nandre Aprila; Ngurah Pandji Mertha Agung Durya; Ajeng Andriani Hapsari; Vivid Violin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Today's smartphones are not just a means to fulfill communication needs; they have now become part of the user's lifestyle. Currently, almost every activity and time is spent using a smartphone, such as working, playing, socializing, or carrying out other daily activities. This study intends to examine how lifestyle, marketing, and product quality affect consumers' purchase choices. The basic data used in this study was collected from questionnaires. Using the judgment sampling method, a total of 100 respondents made up the sample. The method of data analysis employs numerous linear regressions. The findings of the study demonstrate that lifestyle significantly affects purchase choices. The high level of lifestyle can be used to explain this influence. Purchase decisions are significantly influenced by promotions. The effect of the significant amount of promotion of 0.000 can be explained. Purchase decisions are significantly influenced by product quality. The impact of the significant degree of product quality of 0.06 can be discussed. The combination of lifestyle, incentives, and product quality has a big impact on buying choices. The substantial level of lifestyle, promotion, and product quality can be used to explain this influence.